Antimicrobial Effect of Cinnamon Oil Against Oral Microorganisms (Medico Legal Update, 2020)
Background/Objectives: There has been a growing interest in the antimicrobial activity of natural extracts that inhibit the growth of microorganisms without side effects. Therefore, we evaluated the antibacterial effects of cinnamon oil against oral microorganisms existing in dental plaque.Methods/Statistical analysis: Dental plaque was formed on bovine specimens using a growth medium for 6 days, followed by treatment with either 2.5% cinnamon oil, 0.12% chlorhexidine gluconate, or 10% dimethyl sulfoxide for 5 min, twice per day. On day 7, each specimen was imaged using quantitative light-induced fluorescence–digital to assess microbial activity of dental plaque. A one-way analysis of variance and the Scheffe post hoc test were performed to analyze the differences in red/green ratio (R/G values) of dental plaque between the three treatment groups.Findings: The average R/G values of dental plaque was the lowest in the 2.5% cinnamon oil group (1.180 ± 0.010), and these values were significantly different from those of the chlorhexidine gluconate group (1.249 ± 0.008) (p